Royalty sharing, effort and invention in universities : evidence from Portugal and Spain - Arqué-Castells, Pere (2016)
Portuguese and Spanish universities have adopted well-defined royalty sharing arrangements over the last fifteen years. We investigate whether such royalty sharing arrangements have been effective in stimulating inventors’ efforts and in ultimately improving university outcomes. We base our empirical analysis on university-level data and two new self-collected surveys for both inventors and Technology Transfer Offices (TTOs). Evidence from the inventors’ survey indicates that one third of respondents are incentivised by current royalty sharing arrangements, one third could be incentivised by higher royalty shares, and the remaining third is totally insensitive to royalty sharing. Plain regressions on university level datasets suggest that the incentive effects documented by the inventors’ survey fail to translate into increased patenting or licensing income. It would seem that inventor royalty shares are not as influential as they could be, due to the poor commercial prospects of university inventions. Among other possible reasons, these poor prospects appear to reflect the fact that inventors are unable to produce potentially licensable inventions, or that eventually TTOs may not be focussing enough on commercialising their inventions.